2007
DOI: 10.1021/la702091c
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Function, and Stability of Enzymes Covalently Attached to Single-Walled Carbon Nanotubes

Abstract: We describe the structure, activity, and stability of enzymes covalently attached to single-walled carbon nanotubes (SWNTs). Conjugates of SWNTs with three functionally unrelated enzymes-horseradish peroxidase, subtilisin Carlsberg, and chicken egg white lysozyme-were found to be soluble in aqueous solutions. Furthermore, characterization of the secondary and tertiary structure of the immobilized proteins by circular dichroism and fluorescence spectroscopies, respectively, and determination of enzyme kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
1
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 24 publications
9
124
1
14
Order By: Relevance
“…As it can be seen in Table 5, all hydrolases underwent some conformational changes upon immobilization on both nanomaterials, in agreement with what was observed for other supports (Asuri et al, 2007;Cang-Rong and Pastorin, 2009;Karajanagi et al, 2004;Tzialla et al, 2010). The a-helix content of all covalentlyimmobilized enzymes on both nanomaterials increased compared to that of free enzymes.…”
Section: Structural Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…As it can be seen in Table 5, all hydrolases underwent some conformational changes upon immobilization on both nanomaterials, in agreement with what was observed for other supports (Asuri et al, 2007;Cang-Rong and Pastorin, 2009;Karajanagi et al, 2004;Tzialla et al, 2010). The a-helix content of all covalentlyimmobilized enzymes on both nanomaterials increased compared to that of free enzymes.…”
Section: Structural Studiessupporting
confidence: 88%
“…Immobilization yields up to 55% were achieved, which results in an enzyme loading of 1.65 mg of enzyme per mg of nanomaterial. This enzyme loading value is particularly high compared to the published values for other types of carbon-based nanomaterials (Asuri et al, 2007;Cang-Rong and Pastorin, 2009;Karajanagi et al, 2004). In previous work, we have shown that the immobilization yield could be improved by using a lower enzyme to nanomaterial weight ratio, albeit at the expense of the enzyme loading (Pavlidis et al, 2010a).…”
Section: Hydrolase Immobilization On Carbon-based Nanomaterialsmentioning
confidence: 80%
“…Radio-frequency waves can be used in this case because of the particular electronic properties of carbon nanotubes and they are more attractive than the near-infrared laser heating method used in others strategies. Moreover, carbon nanotubes could be derivatized with various proteins to improve their specificity [110]. Indeed, it might be feasible to link these nanotubes to CPPs, to improve their cellular uptake, or to targetingpeptides to concentrate them at the tumor site.…”
Section: Thermal Sensitive Polymersmentioning
confidence: 99%
“…Nonetheless, the introduction of CNTs as bioelectrodes constitutes a major breakthrough in EFC. Other than mediating charge transfer, CNTs have manifested great efficiency in EFC by supplying a strong platform for enzyme immobilization (Fischback et al, 2006;Asuri et al, 2007;Li et al, 2008b;Zhao et al, 2009;Zhou et al, 2009). CNTs allowed enzyme molecules to be covalently attached onto their surface and promote high enzyme loading by permitting crosslinked enzyme aggregate coating (Fischback et al, 2006).…”
Section: Carbon Nanotubes In Biotechnologymentioning
confidence: 99%
“…In addition, the nanoscale environment provided by CNTs could enhance enzyme stability. Enzymes covalently attached onto CNTs were found to have a high degree of stability due to their covalent linkage, which afforded significant resistance against denaturation (Govardhan, 1999;Asuri et al, 2007;Sheldon, 2007). In another point of view, the curvature of CNTs increases the distance between enzyme molecules, thereby reducing detrimental interaction between the enzymes and leading to an increased enzyme stability (Asuri et al, 2006).…”
Section: Carbon Nanotubes In Biotechnologymentioning
confidence: 99%